A diaminomaleonitrile based selective colorimetric chemosensor for copper(ii) and fluoride ions. (29th January 2015) - Jo, Tae Geun; Na, Yu Jeong; Lee, Jae Jun; Lee, Myoung Mi; Lee, Sun Young; Kim, Cheal
Abstract : A chemosensor showed colorimetric sensing for copper(ii ) and fluoride by changing color from yellow to colorless and to orange. Abstract : A new and simple colorimetric receptor1, based on 2, 3-diaminomaleonitrile and julolidine moieties, has been synthesized and characterized.1 showed a selective colorimetric sensing ability for copper(ii ) ions by changing color from yellow to colorless, and could be utilized to monitor Cu 2+ over a wide pH range of 4–12. The detection limit of1 (2.1 μM) for Cu 2+ ions is much lower than that recommended by WHO in drinking water (30 μM). Moreover, the receptor1 can also detect fluoride by color change from yellow to orange, distinguishing the fluoride ions effectively from anions such as CH3 COO − and CN − . It was also found that the1 –F − complex was reversibly bound and could be simply reverted back through treatment with a proper reagent such as HCl. The sensing mechanism for F − was theoretically supported by DFT and TD-DFT calculations.